Using Poem Generator in Writing Poem 11th Grade of MAN Sidoarjo's Students Voice - Agsan Widy Kirana Pradana; Amik Amri Rahmadhi; Zahrotul Laila; Gilang Dwi Prasetyo; Kurnia Setya Rini; Tiara Maula Lestari (Edulitics (Education, Literature, and Linguistics) Journal, 2021)
Latterly, writing poems manually becomes such a hesitating process in the realm of senior high school students. Lack of experience in writing poems is also one of the difficulties for them. Thus, a poem generator namely Poem Generator was conducted to aid students writing poems. This study aimed to describe the students’ voice related to the use of Poem Generator in writing poems. This study is guided under the descriptive qualitative research design through close-ended questionnaires and semi-structured interview to answer the research question. There were 31 students of XI IPA 1 and 2 were involved as the participants in answering the questionnaire and 6 random selected students were also involved in the interview. The result revealed that the majority of students considered the use of Poem Generator helpful in writing poetry instantly. Although the meaning was sometimes difficult to understand, some participants agreed that the Poem Generator website helped them gain new vocabulary and was a fun experience because they got to know new technology.